Os segredos das ervas nos saberes e fazeres das benzedeiras e benzedores da Cidade de Goiás - Campos, Adelbiane Conceição (2021)
This technical report presents the research on the use of herbs in traditional knowledge in the city of Goiás, which aims to map the holders of the profession of blessing and healers/those who have the practice of curing physical and spiritual ailments through knowledge ancestral using medicinal herbs. It was developed in the Line of Research in Heritage Education and Heritage Management of the Graduate Program in Cultural Studies, Memory and Heritage, Professional Master's Degree, at the State University of Goiás - Cora Coralina Campus (PROMEP/UEG. Taking these as the axis of discussion). traditional knowledge as part of the Brazilian Intangible Heritage. The research was carried out from oral interviews with the holders, holders and family members, believing that the latter are agents responsible for the maintenance of the property. memory for being the bearer of the knowledge of those who lived and experienced facts from the past that were sometimes kept, the learning of their ancestors and thus, became responsible for the transfer of such knowledge. Rua da Conceição (Rua do Capim), Alto Santana (urban neighborhood) and in the Santa Bárbara district. active in healing rituals, in the prayers performed during the blessing process and ritualistic relationship with herbs, the different cures performed for certain types of diseases and the process of learning knowledge, in the materialization of bottles made with roots from the cerrado, the unfolding of this work, goes against the proposal of the research line that was offered by this Program, which is Heritage Education and Heritage Management, which will result in the final product as feedback for the researched community. This final product is a printed catalog that contextualizes in summary the history and daily life of each holder, as well as the characterization of each herbs and roots, their healing properties, and the prayers during the blessing ritual revealed by the detainers.It is noteworthy that the trades mentioned are associated with traditional knowledge, supported by Law 13.123, which provides for access to genetic heritage, as well as the sharing of benefits for the conservation and sustainable use of biodiversity.